116 Invasive Lobular Carcinoma of the Breast With Extracellular Mucin Production: A Case Report and Review of the Literature. (11th January 2018) - Carniello, Jose Scarpa; Edelweiss, Marcia
Abstract: Objectives: Invasive lobular carcinoma (ILC) is the second most common histological type of breast carcinoma, accounting for 5%-15% of all invasive breast cancers. Intracellular mucin has been classically described in lobular carcinoma, frequently leading to signet-ring cell morphology. However, extracellular mucin production is usually a feature of ductal carcinoma. We report a case of ILC with extracellular mucin production. Methods: We report a case using clinical data and gross/microscopic pathologic information. H&E-stained slides, immunostains, and fluorescence in situ hybridization (FISH) for Her2 were reviewed. Results: A 65-year-old woman presented with a palpable mass in the left breast. Mammogram evidenced increased density and distortion in the upper lateral periareolar area. Core needle biopsy showed ILC with pleomorphic features, focal signet-ring cells, and extracellular mucin production. ER immunostain was strongly positive in 98% of tumor cells, PR was negative (0%), and Her2 was equivocal (1+/2+). FISH for Her2 was not amplified. The patient underwent left modified radical mastectomy. Gross examination revealed a 3.0 x 2.4 x 2.3 cm, firm, nodular to infiltrating bordered, pink-white mass spanning from the 11 to 2 o'clock position and an adjacent 1.1cm satellite nodule. Microscopic examination showed uniform, dyshesive neoplastic cells with focal pleomorphic nuclear features and signet-ring cell features invading the stroma in a single-file pattern with abundant extracellular mucin production consistent with ILC. Lobular carcinoma in situ with central necrosis, focal mucin production, pleomorphic features, and signet-ring cell morphology was present. Immunohistochemistry for E-cadherin was negative in both invasive and in situ components. Of 15 axillary lymph nodes, 11 were positive for macrometastasis. The patient developed bone metastasis in the sacral area a year after the initial diagnosis. Conclusion: ILC with extracellular mucin production is very rare with few reports described in the literature. Extracellular mucin is not an exclusive feature of ductal phenotype and should not mislead the pathologic diagnosis.